Serum from patients with ankylosing spondylitis can increase PPARD, fra-1, MMP7, OPG and RANKL expression in MG63 cells - Hu, Zaiying; Lin, Dongfang; Qi, Jun; Qiu, Minli; Lv, Qing; Li, Qiuxia; Lin, Zhiming; Liao, Zetao; Pan, Yunfeng; Jin, Ou; Wu, Yuqiong; Gu, Jieruo (Clinics, 2015)
OBJECTIVES: To explore the effects of serum from patients with ankylosing spondylitis on the canonical Wnt/β-catenin pathway and to assess whether the serum has an osteogenic effect in MG63 cells. METHODS: MG63 cells were cultured with serum from 45 ankylosing spondylitis patients, 30 healthy controls, or 45 rheumatoid arthritis patients. The relative PPARD, fra-1, MMP7, OPG and RANKL mRNA levels were measured using quantitative real-time polymerase chain reaction. Associations between gene expression and patient demographics and clinical assessments were then analyzed. RESULTS: MG63 cells treated with serum from ankylosing spondylitis patients had higher PPARD, fra-1, MMP7 and OPG gene expression than did cells treated with serum from controls or rheumatoid arthritis patients (all p